Rice Mill Financial Performance of “Z” in Arah Tiga Village, Lubuk Pinang District, Mukomuko Regency - Efrizal Efrizal; Redy Badrudin; Reswita Reswita (AGRITROPICA : Journal of Agricultural Sciences, 2023)
This research was conducted in Arah Tiga, Lubuk Pinang District, Mukomuko Regency.  The research area was chosen deliberately.  This study was conducted to determine the financial performance of the rice milling company ‘Z'.  Observations were made from February 2020 to March 2020.  This study used primary and secondary data.  Financial performance analysis includes current, solvency, and profitability ratios and asset turnover.  The review results show that the liquidity ratio (CR) averages 4.27.  It means it is safe and very unhealthy.  Thus, the average debt service obligation (DAR) of assets or resources is 26.49%, which means the assets or resources are protected or healthy.  In addition, the average debt service obligation (DER) is 102.87%, which means it is prudent or not profitable.  The Total Assets Ratio (ROA) is an average of 44.84%, which means it is protected, and the Return on Earnings (ROE) is an average of 163.43%.  Because the average FATO value is 0.007, activity performance is classified as unable to increase asset capacity.